Templated Atom‐Precise Galvanic Synthesis and Structure Elucidation of a [Ag24Au(SR)18]− Nanocluster. Issue 3 (27th November 2015) - Bootharaju, Megalamane S.; Joshi, Chakra P.; Parida, Manas R.; Mohammed, Omar F.; Bakr, Osman M.
Abstract: Synthesis of atom‐precise alloy nanoclusters with uniform composition is challenging when the alloying atoms are similar in size (for example, Ag and Au). A galvanic exchange strategy has been devised to produce a compositionally uniform [Ag24 Au(SR)18 ] − cluster (SR: thiolate) using a pure [Ag25 (SR)18 ] − cluster as a template. Conversely, the direct synthesis of Ag24 Au cluster leads to a mixture of [Ag25− x Au x (SR)18 ] −, x =1–8. Mass spectrometry and crystallography of [Ag24 Au(SR)18 ] − reveal the presence of the Au heteroatom at the Ag25 center, forming Ag24 Au. The successful exchange of the central Ag of Ag25 with Au causes perturbations in the Ag25 crystal structure, which are reflected in the absorption, luminescence, and ambient stability of the particle. These properties are compared with those of Ag25 and Ag24 Pd clusters with same ligand and structural framework, providing new insights into the modulation of cluster properties with dopants at the single‐atom level. Abstract : A [Ag24 Au(SR)18 ] − nanocluster was synthesized by a galvanic exchange strategy and characterized using mass spectrometry and single‐crystal XRD. The replacement of the central Ag atom of Ag25 (SR)18 by Au occurs without compromising Ag25 integrity. Subtle changes in the Ag25 structural framework after doping caused significant changes in the stability, electronic, optical, and luminescence properties relative to the properties of the parent Ag25 .